Surgical Management of Urogenital Fistula UGF: Sikasso’s Hospital Eperience - Traore, Salifou; Haidara, Dadé B; Kanté, Moussa; Dembele, Ange M; Dolo, Abdou; Traore, Soumaila; Sanogo, Abdoulaye; Diallo, Aly B; Traore, Bathio; Falaye, Sissoko; Ouattara, Kateneme S; Dembélé, Ousmane; et al. (British Journal of Healthcare and Medical Research, 2024)
Acquired abnormal communication between the urinary and genital tracts. UGF are obstetrical in our context and result from a stagnation of labour in delivery. Whereas they follow urogenital instrumentation and surgical interventions in industrialized countries. [1, 2]. Obstetric fistula involves anatomical lesions whose location, size, number, and depth differ according to the length of time for labour stagnation and the therapeutic modality adopted for its management. There are many existing classifications and, although they are all based on the same parameters, namely: fistula size, location, locoregional trophicity and the possibility of affecting the continence system, none of them is unanimous.